Unusual Case of isolated post-styloid Parapharyngeal Space metastasis in a treated case of Carcinoma Supraglottis: A case Report and Review of literature - Panbude, Sushil N.; Vaidya, Abhishek; Pangarkar, Meena A.; Juvekar, Shashikant L. (Indian Journal of Case Reports, 2022)
Squamous cell carcinoma of supraglottis is common head and neck malignancy, comprising of 30% of laryngeal carcinoma. Supraglottic carcinoma commonly metastasizes to the level II, III and IV cervical nodes and distant metastases are uncommon. Delayed local and regional recurrences are known, local recurrence being more common. We report a case of carcinoma supraglottis with advanced locoregional disease at initial presentation and treated with neoadjuvant chemotherapy followed by chemo-radiotherapy with complete response on post treatment PET-CT scan. Surveillance PET-CT showed an isolated lesion in left post-styloid PPS where neurogenic tumors are more common and isolated nodal metastasis is unusual. We did ultrasound guided FNAC and cytology confirmed presence of metastatic poorly differentiated carcinoma.